What Peace Means for Deforestation: An Analysis of Local Deforestation Dynamics in Times of Conflict and Peace in Colombia - Ganzenmüller, Raphael; Sylvester, Janelle M.; Castro-Nunez, Augusto (Frontiers in Environmental Science, 2022)
Using Colombia as a case study, this analysis provides insights on deforestation dynamics in times of conflict and peace and the different variables that may be driving these dynamics. We performed time series clustering of yearly deforestation data (2001–2018) from 708 out of 1122 mainland Colombian municipalities (accounting for 98% of the total deforestation areas in Colombia) and produced random forest regression models to identify drivers that explain varying, local-level deforestation dynamics. Municipalities were characterized by seven categories of deforestation dynamics, with the Amazon region being largely represented by only four categories and the Andes region displaying all categories of deforestation dynamics. Notably, six of the seven categories exhibit substantial increases in deforestation in the years following the peace agreement. The regression analysis revealed that coca cultivation area, number of cattle, and municipality area are the top three drivers of deforestation dynamics at national, regional, and category levels. However, the importance of the different variables varied according to the different spatial dimensions. Results provide further understanding on how the drivers of deforestation change not only at a regional scale, as assumed by much of the current literature about drivers of deforestation, but also at a lower scale of analysis (intraregional and intradepartmental variation in the case of Colombia). Insights from this study can be used to understand deforestation dynamics in other countries experiencing times of conflict and peace and will support decision-makers in creating programs that align actions for peacebuilding, climate change mitigation, and biodiversity conservation more effectively.